Prevalence of Sleep-Disordered Breathing in Prader–Willi Syndrome - Ahmed Abushahin (17337703) (2023)
Introduction. Sleep-disordered breathing (SDB) is common in patients with Prader–Willi Syndrome (PWS). However, the prevalence of SDB varies widely between studies. Early identification of SDB and factors contributing to its incidence is essential, particularly when considering growth hormone (GH) therapy. Objectives. The aims of the study were to describe the prevalence and phenotypes of sleep-disordered breathing (SDB) in patients with Prader–Willi syndrome (PWS) and to determine the effects of age, gender, symptoms, GH therapy and body mass index on SDB severity. Methods. This study was a retrospective chart review of all patients with genetically confirmed Prader–Willi syndrome who underwent diagnostic overnight polysomnography (PSG) in the sleep laboratory at Sidra Medicine. Clinical and PSG data of enrolled patients were collected. Results. We identified 20 patients (nine males, eleven females) with PWS who had overnight sleep polysomnography (PSG) at a median age (IQR) of 5.83 (2.7–12) years. The median apnea-hypopnea index (AHI) was 8.55 (IQR 5.8–16.9) events/hour. The median REM-AHI was 27.8 (IQR 15–50.6) events/hour. The median obstructive apnea-hypopnea index (OAHI) was 7.29 (IQR 1.8–13.5) events/hour. The median central apnea-hypopnea index (CAHI) was 1.77 (IQR 0.6–4.1) events/hour. Nineteen patients (95%) demonstrated SDB by polysomnography (PSG) based on AHI ≥1.5 events/hour. Nine patients (45%) were diagnosed with obstructive sleep apnea (OSA). Three patients (15%) were diagnosed with central sleep apnea (CSA). Seven patients (35%) were diagnosed with mixed sleep apnea. No correlations were observed between AHI and age, gender, BMI, symptoms, or GH therapy. However, REM-AHI was significantly correlated with BMI ( P = 0.031 ). Conclusion. This study shows a high prevalence of SDB among our patients with PWS. Obstructive sleep apnea was the predominant phenotype. BMI was the only predictor for high REM-AHI. Further studies of large cohorts are warranted to define SDB in PWS and design the appropriate treatment. Other Information Published in: Canadian Respiratory Journal License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1155/2023/9992668